Strategies for promoting reading: ideas and recommendations for implementing reading encouragement workshops - Chaves Salgado, Lorena (2015)
This document presents a guide with recommendations for implementing reading encouragement workshops as a means to promote the development of reading habits and the enjoyment of reading in the lives of children.